Implementasi Clean Architecture Dalam Membangun Aplikasi Mobile Menggunakan Flutter - William Prapdeson Laksono; Bagas Satria Tri Wicaksana; Abdurrahman Yusuf Wijasena; Yoga Sahria (PT. Inovasi Teknologi Komputer, 2024)
Clean Architecture, or better known as Clean Architecture, is a concept in software development that aims to create a software structure that is easy to understand, easy to test, and free from implementation details. So this research will test the development of mobile applications with Clean Architecture which uses BLoC state-management in Flutter-based applications. In the application being tested there are three features, namely the homepage display which displays all articles, the details display which displays details of a selected article and the display of articles that are liked and will be stored in the local database. The Clean Architecture test applied to the application this time was assessed in terms of maintainability of the features contained in the application. Clean Architecture makes it easy for developers to apply and develop a system and divide it into several parts so that they can divide it into a team and work on it together without destroying the main code itself. In terms of maintenance, it is also easier to do because changing a line of code will not damage the entire code that has been built. Application development using Clean Architecture produces good quality code that is maintainable for future development and provides time and load efficiency in the process of working on applications that are built without reducing the quality of the code produced.